From Clicks to Conversions: Mastering Data-Driven Marketing for Maximum ROI - Aditi, Bunga; Wardana, Miko Andi; Yuliani, Erma (Jurnal Informatika Ekonomi Bisnis, 2025)
This study investigates the impact of data-driven decision making and marketing automation using artificial intelligence on return on investment, with customer engagement examined as a mediating variable. Employing a quantitative research design, data were collected through an online survey targeting professionals in digital marketing and e-commerce sectors. The analysis was conducted using Partial Least Squares Structural Equation Modeling, which validated both the measurement and structural models. The results reveal that data-driven decision making and marketing automation using artificial intelligence significantly influence customer engagement, which in turn has a strong and positive effect on return on investment. Furthermore, customer engagement mediates the relationship between both predictor variables and return on investment, suggesting that the financial benefits of digital strategies are maximized when they successfully foster active and meaningful customer interactions. These findings highlight the importance of integrating analytical tools and technological innovations with customer-centric engagement strategies to achieve sustainable marketing performance in digital environments.